An investigation of piezoelectric tile with drop test technique for energy harvesting application - Anis Maisarah Mohd Asry; Farahiyah Mustafa; Sim Sy Yi; Maizul Ishak; Aznizam Ahmad (Institute of Advanced Engineering and Science, 2023)
This paper present test and analyses of piezoelectric transducers tile with drop test technique. This piezoelectric tile was tested together with bending mechanism. The bending mechanism was designed using SolidWork software and manufactured by employing 3D printer technology to conduct the evaluation. The piezoelectric transducers connected in a parallel configuration and inserted in piezoelectric tile together with bending mechanism. The drop test employed to test this piezoelectric tile with various loads and speeds. This test conducted based on free fall concept. A wooden box used as a guide to drop an object onto the piezoelectric tile. The various weight load released at a fixed height with different speeds. The output power generated based on the weight and speed of the object were recorded with average force applied on piezoelectric transducer. The highest output power generated was 634.54 ÂµW when 6 kg load released at 2 drop/s with 1.89 N average force applied on each piezoelectric transducer. The lowest output power generated was 6.28 ÂµW when 1 kg load released at 0.5 drop/s with 0.22 N average force applied. The results showed good output power of the piezoelectric transducer was generated for energy harvesting application.